The reflections of individualism and collectivism on verbal communication styles in American English and VietNamese = Sự phản ánh giá trị cá nhân và giá trị cộng đồng trong giao tiếp nói tiếng Anh mỹ và tiếng Việt - Nguyễn, Thị Ngọc Diệp (2020)
The values of individualism and collectivism have been proved to exert profound effects on many aspects of life respectively in America and Vietnam, among which is the two groups of people’s verbal communication styles. However, it seems that this interesting topic has yet to be widely explored. By employing the questionnaires to collect data from 40 European American and Vietnamese informants, the study demonstrates their understandings of the dominant value in their society, as well as how it is reflected in their language use in terms of directness or indirectness, formality or informality. The result confirms the exploitation of directness in American conversations as a manifestation of individualism. Nevertheless, it also re-questions the popular remark that indirectness and formality – signs of collectivism are preferred by Vietnamese interlocutors and the same as European American ones with informality – sign of individualism, as the dependence is on specific situations. Finally, some cross-cultural recommendations are given with the hope to enhance mutual understandings between two groups of people when they communicate with one another